A description of the second species of the genus Platybolium Blair, 1938 (Coleoptera: Tenebrionidae) collected from a nest of Pheidole singaporensis Özdikmen, 2010 (Hymenoptera: Formicidae) in Thailand - Maruyama, Munetoshi; Sasitorn, Hasin; Ando, Kiyoshi (Zootaxa, 2023)
Platybolium watanai sp. nov., the second species of the genus, is described from Thailand, with illustrations of the diagnostic characters, including the defensive glands and the cuticular structures of females. The type species of the genus, Platybolium alvearium Blair, 1938, is known from beehives in a wide range of the Oriental region, but the new species was found in an ant nest of Pheidole singaporensis Özdikmen, 2010. Myrmecophily in the new species is discussed.